KETERKAITAN PENGELUARAN PEMERINTAH DAN INVESTASI SWASTA TERHADAP PEREKONOMIAN KOTA PALEMBANG (INPUT - OUTPUT ANALISIS) - Nova Murbarani (Department of Development Economics, Universitas Sriwijaya, 2009)
The purpose of this research is to know the linkage of government expenditure and the private investment to output and the gross of value added in Palembang city. The analysis technique used is the input-output model. This research analyze the secondary data which is form the private investment data and the input-output of table of Palembang city in 2006.The result of this research shown that the manufacturing industry sector trading, hotel, and restaurant sectors were the strategic sector in the development plan in Palembang city, that's shown by the multiplier effect of government expenditure, the establishment constant financial capital and the private investment every rupiah increase in manufacturing industry factor, it will increase the biggest output in manufacturing industry sector in the amount of 1,20979 rupiah, and the smallest output increase in agriculture sector is only 0,00186 rupiah. The increase of the biggest gross value added in manufacturing industry sector is 0,52773 rupiah, and the smallest gross value added also in the agriculture sector that is 0,00143 rupiah. The biggest power of dispersion index is in the manufacturing industry sector that is 1,15032, it can push the development of the backward sectors. The biggest degree of sensitivity index also is manufacturing industry sector is 1,45350, it can stimulate the development of the forward sectors. The smallest power of dispersion index and the degree of sensitivity index are in the mining in amount of 0,80058, it's means that sector doesn't have the strong power in influencing the generally activity of economy. Keyword:Government Expenditure, Private Investment, Multipliers Effect, Forward and Backward Linkage.